2019
DOI: 10.15517/am.v30i2.33221
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of arbuscular mycorrhizal fungi inoculated on Canavalia ensiformis L. in Calcaric Histosol soils

Abstract: Introduction. In recent years, significant results have been obtained in Cuba in the joint management of efficient strains of arbuscular mycorrhizal fungi (AMF) and Canavalia ensiformis L., in different types of soils. However, there are no reports about the effectiveness of strains of AMF in Calcaric Histosol soils, which are highly represented in the central and eastern areas of the country. Objective. The objective of this research was to compare the effectiveness of four AMF strains inoculated in C. ensifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
0
2
1
Order By: Relevance
“…Our results confirmed that the effects on plant shoot, root, and total biomass increased with RLC. RLC directly determines the nutrient exchange ratio between plants and AMF ( Smith et al., 2009 ; Bücking et al., 2012 ; Simó-González et al., 2019 ); however, our results did not support RLC being the most important moderator predicting the effects of AMF on plant biomass based on such a large dataset across different experimental settings and biotic and abiotic factors. Generally, the relationship between RLC and experimental duration is not linear but curved ( Antonio and Nogueira, 2003 ; Samiappan and Manian, 2009 ), which demonstrates that RLC may have better predictive value on effect size at a relatively short time duration, but not the entire duration, especially when compared to the effect of experimental duration.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Our results confirmed that the effects on plant shoot, root, and total biomass increased with RLC. RLC directly determines the nutrient exchange ratio between plants and AMF ( Smith et al., 2009 ; Bücking et al., 2012 ; Simó-González et al., 2019 ); however, our results did not support RLC being the most important moderator predicting the effects of AMF on plant biomass based on such a large dataset across different experimental settings and biotic and abiotic factors. Generally, the relationship between RLC and experimental duration is not linear but curved ( Antonio and Nogueira, 2003 ; Samiappan and Manian, 2009 ), which demonstrates that RLC may have better predictive value on effect size at a relatively short time duration, but not the entire duration, especially when compared to the effect of experimental duration.…”
Section: Discussioncontrasting
confidence: 89%
“…Our results confirmed that the effects on plant shoot, root, and total biomass increased with RLC. RLC directly determines the nutrient exchange ratio between plants and AMF (Smith et al, 2009;Bücking et al, 2012;Simo-Gonzaĺez et al, 2019); however, our results did not support RLC being the most important moderator predicting the effects of AMF on plant biomass based on such a large dataset across different experimental settings and biotic and abiotic factors.…”
Section: A B Ccontrasting
confidence: 91%
“…En un suelo Húmico Carbonatado con pH (H 2 O) entre 7,80 a 7,90 la canavalia no presentó respuesta significativa a la inoculación con INCAM-2; sin embargo, la aplicación de INCAM-11 incrementó significativamente la masa seca aérea en un 83,5% en comparación al tratamiento control (Simó et al 2019); lo cual evidencia la importancia de realizar esta investigación para las condiciones edáficas donde se desarrolló.…”
Section: Resultados Y Discusiónunclassified